Research cruise of the Scandinavian South African Antarctic expedition, December 1997 to February 1998 - Froneman, P.W.; Pakhomov, Evgeny; Turner, D.; Abrahamson, K.; Karlsson, B.; Godhe, Anna; Bertilsson, Stefan; Graneli, Wilhelm; Carlsson, Per; Wängberg, Sten-Åke; Wulff, Angela; Croot, Peter; et al. (South African Journal of Science, 1998)
Focuses on the Scandinavian/South African Antarctic expedition conducted between December 4, 1997 to February 6, 1998 which determined the role of Southern Ocean in the global carbon cycle in physical and biological oceanographic studies. Aims of the expedition; Underway sampling conducted; Biological results of the expedition; Conclusions.
Keywords: NARE ekspedisjoner; Sørishavet; fytoplankton; krill; marin biologi; oseanografi

Glaciological studies by Landsat imaginery of perimeter of Dronning Maud Land, Antarctica - Orheim, Olav (Results from Norwegian Antarctic Research 1974-1977, 1978)
Keywords: Dronning Maud Land; NARE ekspedisjoner; geologi; glasiologi; havis; isbreer

Results from Norwegian Antarctic research 1974-1977 - Polarinstitutt, Norsk (1978)
Publication Title: Norsk Polarinstitutt. Skrifter
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner

Norwegian Antarctic Research. Past and Present. - Orheim, Olav (University of Chile, 1977)
Pages: 154-160 Publication Title: El desarrollo de la Antártica Place: Punta Arenas, Chile
Keywords: Antarktis; Bouvetøya; Dronning Maud Land; NARE ekspedisjoner; Weddellhavet; geologi; glasiologi; havis; hvalfangst; kongress; marin biologi; marin geofysikk; marin geologi; meteorologi; oseanografi; symposium